Systemic conception of controlling - Volker Ahrens (Nordakademie - Hochschule der Wirtschaft, 2019)
Controllers often seem to be concerned among themselves with the question of what role they play in companies and what tasks they have to perform. This article follows this discussion from the perspective of an outsider on the one hand and from a systems theoretical perspective on the other. Firstly, the structure of business organization needs to be modernized. In it, controlling should have the function of structurally coupling political leadership and economic value creation.
Keywords: 330